Basic Fourth Grade Pupils’ Attitudes towards Assigned Tasks in Social Studies Subject and its Relationship with Achievement Goals Orientation (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study aimed at assist the level of Attitudes towards assigned tasks in social studies subject and achievement goals orientation to basic fourth grade pupils, and the relationship them.For that, the descriptive method was used, and prepared a reliable validate scales to measure attitudes towards assigned tasks in social studies subject and achievement goals orientation. The simple random sample consisted of (299) males and females pupils in Lattakia City schools.The results showed that pupils’ attitudes towards assigned tasks were positive in general, and the level of Achievement Goals Orientation overall was high.  Goal (Mastery-Approach ranked first, followed by (Performance-Approach), followed by (Mastery-Avoidance), and (Performance-Avoidance) ranked last. In addition, There were correlational relationship between that pupils’ attitudes towards assigned tasks in Social Studies Subject and Achievement Goals Orientation overall and its sub-domain (Performance-Approach, Mastery-Approach), but there were no correlational relationship between pupils’ attitudes towards assigned tasks and Goals (Mastery-Avoidance, Performance-Avoidance).So, the research recommended in the light of the results of study to Necessity of the use of Achievement Goals Orientation and Attitudes towards Assigned Tasks among pupils for development of learning outcomes in Social Studies Subject.